2010
DOI: 10.1063/1.3432265
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and micro-luminescence mapping of Xe-implanted defects in diamond

Abstract: Ion implantation in diamond creates optically active defects which have emission lines in broad spectral regions, and may be used in advanced photonics and optical communication applications. A brief review of the photoluminescence properties of Xe + ion implanted diamond is presented. The Xe-related center is of particular interest as this center is one of a few centers (Ni, Si, Cr) in diamond having sharp emission lines in the infrared spectral region, specifically at 813 and 794 nm. The paper discusses an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Recent studies of such centres include chromium- 17,18 , xenon- 19 nickel- 20 and possibly oxygen-related centres 21 , as well as the negatively charged silicon-vacancy (SiV) centre [22][23][24] . The latter has the advantage of being the brightest reported colour centre in diamond 24 .…”
mentioning
confidence: 99%
“…Recent studies of such centres include chromium- 17,18 , xenon- 19 nickel- 20 and possibly oxygen-related centres 21 , as well as the negatively charged silicon-vacancy (SiV) centre [22][23][24] . The latter has the advantage of being the brightest reported colour centre in diamond 24 .…”
mentioning
confidence: 99%
“…32 Commercially produced nanodiamonds would be doped with Xe using ion implantation, as discussed above. 12,13,33 Coreshell structures have also been demonstrated using scalable techniques like fiber drawing, but further investigation may be needed to successfully incorporate nanodiamonds. 34 In conclusion, we have demonstrated that the core-shell Mie resonant structures offer a significant enhancement of emission rates of embedded single defect sources.…”
Section: Fig 4 (A)mentioning
confidence: 99%
“…Also, at room temperature, the excited state does not radiatively decay exclusively through a single ZPL transition; instead, another ZPL line with r À r electric dipole (ED) transition at k ¼ 793 nm emerges. 13 The ratio of emission rates depends on polarization of the main and spurious ZPL lines 13 and is about P(812 nm)/P(793 nm) ¼ 5 for the spectrum shown in Fig. 1(c) in red.…”
mentioning
confidence: 97%
See 2 more Smart Citations